Glutamate Transporter Homolog-based Model Predicts That Anion-π Interaction Is the Mechanism for the Voltage-dependent Response of Prestin - Lovas, Sándor (J Biol Chem, 2015)
Prestin is the motor protein of cochlear outer hair cells. Its unique capability to perform direct, rapid, and reciprocal electromechanical conversion depends on membrane potential and interaction with intracellular anions. How prestin senses the voltage change and interacts with anions are still unknown. Our three-dimensional model of prestin using molecular dynamics simulations predicts that prestin contains eight transmembrane-spanning segments and two helical re-entry loops and that tyrosyl residues are the structural specialization of the molecule for the unique function of prestin. Using site-directed mutagenesis and electrophysiological techniques, we confirmed that residues Tyr(367), Tyr(486), Tyr(501), and Tyr(508) contribute to anion binding, interacting with intracellular anions through novel anion-π interactions. Such weak interactions, sensitive to voltage and mechanical stimulation, confer prestin with a unique capability to perform electromechanical and mechanoelectric conversions with exquisite sensitivity. This novel mechanism is completely different from all known mechanisms seen in ion channels, transporters, and motor proteins.